2021
DOI: 10.1007/s10924-021-02306-z
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Sodium Alginate/Gum Arabic Based Films Enriched with Syzygium cumini Seeds Extracts for Food Application

Abstract: Biodegradable sodium alginate/gum Arabic (SG) films were obtained. The influence of Syzygium cumini seeds extract (SCSE) incorporation in SG films on morphological structure, polymer interaction, thermal behavior, antioxidant activity and physical characteristics were investigated. Moreover, the fabricated films were tested as wrapping materials to extend the shelf life of sunflower oil. Scanning electron microscopy micrographs showed heterogeneous and rough surface after incorporation by SCSE. Possible cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 49 publications
9
24
0
Order By: Relevance
“…Innovations in sustainable food packaging appear as a way to minimize the environmental problems of petrochemical polymers. In this scenario, biopolymers offer the advantages of being produced from renewable resources and/or reintegrated into the carbon cycle through biodegradation by microorganisms and enzymes in a natural environment or compost [9,10]. Among biopolymers, polylactide (PLA) is a linear aliphatic polyester obtained from carbohydrate-rich plants, such as corn or wheat.…”
Section: Introductionmentioning
confidence: 99%
“…Innovations in sustainable food packaging appear as a way to minimize the environmental problems of petrochemical polymers. In this scenario, biopolymers offer the advantages of being produced from renewable resources and/or reintegrated into the carbon cycle through biodegradation by microorganisms and enzymes in a natural environment or compost [9,10]. Among biopolymers, polylactide (PLA) is a linear aliphatic polyester obtained from carbohydrate-rich plants, such as corn or wheat.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that this environmental impact has led to undesirable consequences on marine fauna, the climate, human health and even the economy. Additionally, the benefits of these biodegradable materials in terms of their renewable origin, safety, low cost and potential role for extending the shelf life and maintaining the quality of many food products have to be taken into account [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain active biodegradable films, active compounds are usually incorporated so as to confer antimicrobial and antioxidant properties on the final blend films [ 2 , 7 , 8 , 12 ]. Of the active compounds, phenolic acids, such as ferulic acid, p -coumaric and protocatechuic acids [ 13 , 14 , 15 , 16 , 17 , 18 ], have demonstrated significant antimicrobial and antioxidant properties while exhibiting a milder sensory impact than other natural compounds extracted from plants, such as essential oils.…”
Section: Introductionmentioning
confidence: 99%
“…This further supports the hypothesis of the formation of sodium salts during the solubilization of the extracts in a sodium hydroxide (0.5% NaOH). Therefore, the formation of this color could represent a negative aspect for their incorporation in active food packaging depending on the addition level in the final film [ 6 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Active packaging systems are designed to promote interactions between the packaging itself, the food, and the internal environment. In this framework, natural extracts represent a valuable source of bioactive compounds, such as polyphenols, characterized by well documented in vitro and in vivo antioxidant and antimicrobial properties [ 3 , 4 ] and they can be incorporated in or coated on food packaging materials to prevent microbial development, reduce lipid oxidation, and thereby extend the shelf-life of packaged foods [ 4 , 5 , 6 ]. Natural extracts can be obtained from different natural sources, such as fruits (e.g., grape and pomegranate), herbs and spices (e.g., tea, rosemary, oregano, and cinnamon), or, in a more sustainable view, from plant by-products, such as grapefruit seeds, grape pomace, orange peels, green tea and olive leaves, which are valued for their high functionality and/or bioactivity [ 1 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%